The book that proves time travel happens - Clark, Henry, 1952- (Little, Brown and Company, 2015)
Twelve-year-olds Ambrose, Tom, and Frankie are transported to the boys' hometown of Freedom Falls, Ohio, in 1852 when Frankie blows her Romani family's magical trombone, and to return home they'll have to use both Morse code and the ancient form of divination known as the I-ching.